2018
DOI: 10.1016/j.dib.2018.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Survey dataset on factors that influence satisfaction of clients with architectural services in Lagos State, Nigeria

Abstract: The retention of clients of professional service practitioners is often dependent on their satisfaction with the services they obtain. This article presents data on the factors that influence the satisfaction of clients with architectural services in Lagos State, Nigeria. Data were obtained from a cross-sectional survey research, which adopted random sampling of clients from six estates in the State. The questionnaire was used as an instrument for the survey. The response rate was 81.3%. The dataset is made av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
4
2
0
Order By: Relevance
“…Therefore, the availability of an effective design process can significantly increase the performance of architects. The result is consistent with the findings of Oluwatayo et al (2018), who found that competency, ability to understand and fulfilment of the needs of clients are amongst the top factors that influence their satisfaction towards architectural service.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the availability of an effective design process can significantly increase the performance of architects. The result is consistent with the findings of Oluwatayo et al (2018), who found that competency, ability to understand and fulfilment of the needs of clients are amongst the top factors that influence their satisfaction towards architectural service.…”
Section: Resultssupporting
confidence: 91%
“…Results reveal significant and positive relationships between working condition, organisational support and effective design process and the performance of architects. The strongest effect is obtained from the influence of effective design process on the performance of architects, thereby confirming the studies of Oyedele (2010), Young and Young (2012) and Oluwatayo et al (2018).…”
Section: Resultssupporting
confidence: 84%
“…When the results about consultant selection are compared with the previous studies' findings, similarities are observed. In previous studies, high significance was assigned to price ( Oluwatayo et al, 2018;Sporrong, 2011), previous performance (Ng, 2004;Oluwatayo et al, 2018), being creative and innovative (Ling, 2003), and reputation (Ling, 2003;Oluwatayo et al, 2018). In contractor selection, high importance was assigned to past experience (Enshassi et al, 2013;Plebankiewics, 2010;Watt et al, 2010), price (Enshassi et al, 2013;Watt et al, 2010) which were all similar to the current study's findings.…”
Section: Design Consultant and Contractor Selection Criteria (Aggrega...supporting
confidence: 73%
“…The authors developed a multi-criteria evaluation model to guide the developers in selecting design consultants. Oluwatayo et al (2018) presented data on the factors that influence the satisfaction of clients with architectural services and found the specific areas that the clients are not satisfied with their architects.…”
Section: Introductionmentioning
confidence: 99%
“…These figures are consistent with similar previous studies (Adunola & Ajibola, 2016;NBS, 2014;Oluwatayo et al, 2018). Information on the respondent's gender, age, and qualification was not collected because the questionnaires were generally completed by couples who had co-ownership of the building.…”
Section: Stage Threesupporting
confidence: 88%